Partisipasi stakeholder dalam pengelolaan pariwisata warisan budaya di kawasan Ratu Boko, Yogyakarta - Slamet Suyoto, Rahmat; Wardoyo, Edhi; Susianti, Susianti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to determine the effect of the implementation of Sapta Pesona in the Ratu Boko Region on the comprehension of domestic tourists. The role of the Ratu Boko area is not just the city center, but also a major tourism asset for the city of Yogyakarta, even Indonesia. Ratu Boko's attraction is not only the place, but the atmosphere of life is also a special attraction, which is not found in other places. Thus, the Ratu Boko Region bears various burdens, competing for dominance with one another. As a consequence, there has been a shift in function from cultural space to commercial space, a process that has taken place since the 1980s, which is characterized by the development of large-scale trading and service activities, land disputes between residential and commercial areas which, if not careful, can lead to prolonged conflicts. In this study, the variable studied was the implementation of Sapta Pesona among street vendors. Based on the results of statistical tests with a significance level of 5%, overall (simultaneously) the variables safe, orderly, clean, comfortable, beautiful, friendly and memorable have a significant effect on tourist comprehension. Based on the results of the questionnaire from 100 respondents, it was concluded that the average tourist comprehension of the implementation of Sapta Pesona among the street vendors of Ratu Boko Yogyakarta tends to be poor (close to negative).